2019
DOI: 10.1097/bpb.0000000000000577
|View full text |Cite
|
Sign up to set email alerts
|

The increase of anterior pelvic tilt after semitendinosus transfer to distal femur in patients with spastic diplegic cerebral palsy

Abstract: The aim of this study was to compare semitendinosus transfer to distal femur (STTX) to semitendinosus surgical lengthening (STL) regarding the increase of anterior pelvic tilt after flexed knee gait treatment. Thirty-nine patients were evaluated, and they were divided according surgical procedures at knees: STL group (22 patients/44 knees), which included patients who received medial hamstrings surgical lengthening as part of multilevel approach, and STTX group (17 patients/34 knees), which was represented by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…More recently, however, there has been an increase in articles related to HST surgery. [43][44][45][46][47][48][49][50][51] From a theoretical basis, transfer of ST to the adductor tubercle may have the following advantages over HSL. It converts a two-joint muscle to a one-joint muscle, thereby simplifying its action.…”
Section: Hamstring Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, however, there has been an increase in articles related to HST surgery. [43][44][45][46][47][48][49][50][51] From a theoretical basis, transfer of ST to the adductor tubercle may have the following advantages over HSL. It converts a two-joint muscle to a one-joint muscle, thereby simplifying its action.…”
Section: Hamstring Transfermentioning
confidence: 99%
“…46,47 Of the nine more recent studies in the literature reporting the outcomes of ST transfer, five studies compared HSL and HST and four reported HST only. [45][46][47][48][49][50][51] However, the studies were heterogeneous in terms of inclusion criteria, including GMFCS levels, as well as concomitant transfers and inclusion/exclusion of lateral HSL. The results were mixed, and some longitudinal studies from the same institution demonstrated that early differences between the HST and HSL groups dissipated over time.…”
Section: Hamstring Transfermentioning
confidence: 99%
“…Despite good short- and mid-term results after hamstring lengthening, deterioration in gait and recurrence of flexed knee gait have been reported [ 8 ]. A further side effect of hamstring lengthening is an increase in anterior pelvic tilt, which might mediate the recurrence of flexed knee gait [ 9 , 10 , 11 ]. Attempts to convert the muscle group into a monoarticular function also showed no improvement in pelvic inclination [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research also notes unintended consequences of increased anterior pelvic tilt after distal femoral extension osteotomies, patella tendon shortening, HSL, hamstring transfers, and combination procedures. 6,7,9,[11][12][13][14] Increased anterior pelvic tilt is correlated with increased lumbar lordosis, back pain, and increased energy expenditure during gait 18 and is not part of the natural history of gait for children with CP, 19 making surgeons cautious about performing surgeries after which this can occur. ADFH has been growing in use for skeletally immature children with fixed knee flexion deformities and flexed knee gait, due to it being less invasive and having a shorter recovery time than distal femoral extension osteotomies.…”
mentioning
confidence: 99%
“…There are several surgical options in the treatment of fixed knee flexion deformities and flexed knee gait, including distal femoral extension osteotomy with or without patellar tendon shortening/advancement, 6–8 patella tendon shortening/advancement alone, 9,10 hamstring lengthening (HSL), 11,12 hamstring transfer, 13,14 anterior distal femoral hemiepiphysiodesis (ADFH), 15,16 or a combination of bony and soft tissue procedures 17 with improvement in static and dynamic knee extension reported. Research also notes unintended consequences of increased anterior pelvic tilt after distal femoral extension osteotomies, patella tendon shortening, HSL, hamstring transfers, and combination procedures 6,7,9,11–14 . Increased anterior pelvic tilt is correlated with increased lumbar lordosis, back pain, and increased energy expenditure during gait 18 and is not part of the natural history of gait for children with CP, 19 making surgeons cautious about performing surgeries after which this can occur.…”
mentioning
confidence: 99%